2020
DOI: 10.3389/fpsyg.2020.607000
|View full text |Cite
|
Sign up to set email alerts
|

No Cutting Corners: The Effect of Parental Involvement on Youth Basketball Players in Israel

Abstract: This paper explores the nature of parental involvement in youth basketball in Israel with regard to parenting style and in the context of dilemmas and ethical issues. It is well established that parental involvement in their child’s sporting activity has vast implications on the child’s motivation and enjoyment. With reference to Israeli society, only a few studies have focused on this subject. In order to address this lacuna, we used two questionnaires, given to 173 youth basketball players (child questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Regarding family and the process through which young athletes learn the values and norms of sports culture, children’s experiences can be molded based on their exposure to motivational, cognitive, and affective responses ( Harwood et al, 2019 ). Family influences also affect young athletes’ embrace of positive values and satisfaction, and their approach and comportment, in times of stress, toward sport and physical activity ( Tamminen et al, 2016 ; Lev et al, 2020 ). In this regard, a recent study ( Danioni et al, 2017 ) showed that adolescent athletes whose parents endorsed core values in sport gave great importance to competence values (e.g., skillsets and accomplishments) and moral values (e.g., living up to obligations and fairness), but attributed little importance to status values (e.g., titles and winning).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding family and the process through which young athletes learn the values and norms of sports culture, children’s experiences can be molded based on their exposure to motivational, cognitive, and affective responses ( Harwood et al, 2019 ). Family influences also affect young athletes’ embrace of positive values and satisfaction, and their approach and comportment, in times of stress, toward sport and physical activity ( Tamminen et al, 2016 ; Lev et al, 2020 ). In this regard, a recent study ( Danioni et al, 2017 ) showed that adolescent athletes whose parents endorsed core values in sport gave great importance to competence values (e.g., skillsets and accomplishments) and moral values (e.g., living up to obligations and fairness), but attributed little importance to status values (e.g., titles and winning).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 and Table 3 summarize the results obtained. In general, direct parental involvement through modeling ( Alia et al, 2013 ; Sterret et al, 2013 ), the participation of parents and children together in sports ( Lev et al, 2020 ; Yazeedi et al, 2021 ), and the indirect participation in PA (advice sheets making or newsletters) ( Verhees et al, 2020 ) may promote active lifestyles. It is usual that when PS raises children with parental support ( Yaffe, 2018 ) and affection ( Huffman et al, 2018 ), adequate levels of PA practice are registered.…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, Yazeedi et al (2021) verified that parents who reduced network consumption (modeling) made it easier for their children to adopt the same behavior. On the other hand, Lev et al (2020) highlight co-participation with children in PA as a form of direct parental involvement. Lev et al (2020) found that parents who exercised with their children helped perceive greater enjoyment during PA and, consequently, the children’s participation in it increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of parental modelling appears to be larger on parents and children of the same sex. The recent study has demonstrated that parental support has positive impact on children's engagement in sports (Lev et al, 2020). Another study has revealed that gender plays a major impact in sports, and in recent years, boys have been more likely to participate in these activities than women.…”
Section: Discussionmentioning
confidence: 99%